Stability Of a Delayed Predator-Prey Model With Predator Migration - Sholihah, Nianatus; Kusumastuti, Ari (Proceedings of the International Conference on Green Technology, 2017)
The predator-prey model is one of the interaction models between at least two types of species in the form of ordinary nonlinear differential equations. In this model, based on the availability of prey then we add of time delay with predator migration to describe biological control. In this paper, We will analyze the existance and stability of equilibria. The main theoritical results are perform numerical simulations on changes in the initial value of a population to determine the extent to which human control is done as a predator migration.